Integrating Parent–Teacher Collaboration into a Deep Learning Approach for Numeracy Skills: A Needs Assessment Study - Intan Sari Rufiana; Slamet Arifin; Fierda Nursitasari Amaliya; Mohammad Yusuf Randy; Fina Zulfa Mustafidah (Al Ibtida: Jurnal Pendidikan Guru MI, 2026)
Background: Fostering numeracy through deep learning requires teachers and parents to work together. This partnership cultivates meaningful learning experiences. Although existing literature explores numeracy, parental involvement, and deep learning separately, little research addresses the specific needs of teachers and parents as a basis for collaboration. Aims: This study seeks to analyze what teachers and parents require to implement deep learning in primary school numeracy instruction. Methods: The study used a descriptive mixed-methods approach. Seven teachers and eighty primary school parents participated. Data came from structured questionnaires and semi-structured interviews. The researchers analyzed the data using descriptive statistics and qualitative techniques, including data reduction, display, and drawing conclusions. Results: The findings show that teachers view numeracy as essential, but instruction is still mostly conventional. Deep learning is not yet consistent. Teachers cited time constraints, a lack of operational guidelines, and low parental engagement at home as main obstacles. On the other hand, parents help with studies, but focus mostly on homework, not contextual numeracy activities. Parents also struggle with limited time, a lack of understanding of numeracy concepts, and few practical home-learning manuals. Conclusion: These insights provide a foundation for developing a collaborative deep learning model that links teacher and parent roles to strengthen numeracy education in primary schools.